2007
DOI: 10.1681/asn.2006070770
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term, High-Dosage Candesartan Suppresses Inflammation and Injury in Chronic Kidney Disease

Abstract: Recent evidence suggests that higher-than-usual antihypertensive dosages of renin-angiotensin-aldosterone system blockers may provide additional protection from progression of chronic renal disease; however, there have been few long-term studies, and the underlying mechanisms remain uncertain. This study examined the effects of long-term (14 mo) administration of ultrahigh dosages of the angiotensin receptor blocker candesartan on the progression of renal injury in spontaneously hypertensive rats (SHR). Beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 45 publications
2
38
0
1
Order By: Relevance
“…Prostaglandins generated by the glomerular COX-2 enzyme play an important role in counterbalancing the vasoconstrictory effects of AngII and are, furthermore, implicated in tubuloglomerular feedback mechanism (22). Importantly, in addition to regulation of intrarenal vascular tone and water hemostasis, PGE 2 elicits several growth-promoting and proinflammatory effects initiated by AngII (15,22,63). The AT 1 receptor, which is the primary receptor for AngII in MC, can activate multiple signaling pathways including Ras, the MAPKs, the PI3K, the Akt/PKB kinase, and PKC, respectively (3).…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins generated by the glomerular COX-2 enzyme play an important role in counterbalancing the vasoconstrictory effects of AngII and are, furthermore, implicated in tubuloglomerular feedback mechanism (22). Importantly, in addition to regulation of intrarenal vascular tone and water hemostasis, PGE 2 elicits several growth-promoting and proinflammatory effects initiated by AngII (15,22,63). The AT 1 receptor, which is the primary receptor for AngII in MC, can activate multiple signaling pathways including Ras, the MAPKs, the PI3K, the Akt/PKB kinase, and PKC, respectively (3).…”
Section: Discussionmentioning
confidence: 99%
“…Conceding with our findings, candesartan suppressed the renal MCP-1 and NF-jB in a model of chronic kidney disease. 34 Chen et al 35 showed the anti-inflammatory effects of candesartan through a direct antioxidant action independent of ARB. They postulated that candesartan has the ability to inhibit ROS production and to correct the redox imbalance induced by TNF-a.…”
Section: 17mentioning
confidence: 99%
“…The salutary effect of rennin-angiotensin system blockade is not only caused by its antihypertensive/hemodynamic actions, but also by its ability to reduce oxidative stress, inflammation, and fibrosis, which are major mediators of progression of renal disease (Esteban et al, 2003;Remuzzi et al, 2005;Hayashi et al, 2010). Several studies have demonstrated activation of the intrarenal angiotensin system marked by concomitant up-regulation of angiotensin II and AT1 receptor expression along with activation/upregulation of oxidative, inflammatory, and fibrogenic pathways in the diseased kidney and their amelioration with angiotensin blockade (Gonçalves et al, 2004;Xu et al, 2005;Vaziri et al, 2007;Yu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%